Pengolahan Limbah Cair Produksi Manisan Pada Operasi Pencucian Getah Di UD. Yuasa Food Berkah Makmur- Jawa Tengah - , AKHLISUL WAFI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Production of candied fruit carica has some contaminant or waste is liquid waste, solid waste and waste gas. Liquid waste UD.Yuasa Food Berkah Makmur potential to contamination. The need for a waste treatment facility as environmental protection efforts. Processing units used in UD.Yuasa Food Berkah Makmur is the deposition bath. This is done as an effective efforts by UD.Yuasa Food Berkah Makmur in managing the environment by applying the concept of cleaner production. The goal of tugas akhir, to describe the control process wastewater at UD. Yuasa Food Berkah Makmur and effluent quality standard that is used. Wastewater Quality Standards Central Java Province no. 10 of 2004. The method used this report is to analyze the parameters of liquid waste by taking some samples of wastewater immersion carica fruit sap. The method used is the BOD and COD volumetric, gravimetric at TSS and pH by using a pH stick manual methods. Capacity of the existing settling basin at UD. Yuasa Food 12,400 m3 which can make the process of precipitation with 2.5 hours obtained from waste water discharge per hour is 6480 liters / hour. Results obtained from the deposition bath parameters calculation Biological Oxygen Demand (BOD) 80 mg/L, Total Suspended Solid (TSS) 150 mg/L, pH 6, Chemical Oxygen Demand (COD) 2662 mg/L. The efficiency of each parameter is more than 80% on BOD and TSS, COD, while still far from the standard. Evaluation needs to be done on the method wastewater treatment plant UD. Yuasa Food and shape up.